ONLINE LEARNING IMPLEMENTATION - Dedi Irwan (Universitas Muhammadiyah Kalimantan Timur, 2021)
ABSTRACT This research aimed to find out how online learning implementation affected learning practices in a senior high school in an undeveloped regency in West Kalimantan Province. Descriptive quantitative method was applied in this research. To collect the data, students’ and teachers’ questionnaire were used. The questionnaires adopted Likert scale with five options. The populations of this research were 150 students and 40 teachers, while the sample involved were 90 students and 40 teachers all together. The student sample were selected using simple random sampling. Overall, this research found that both teachers and students had similar views regarding the application of the online learning policy during covid 19 pandemic. In this regard they agreed to claim that the online learning implementation tended to show more negative influence than positive to almost all classroom learning processes. The average percentage of teachers and student who found the negative impacts of the online learning policy implementation were, respectively, 50.8% and 73.86%. Nonetheless, the percentage proportion of students who did not claim the implementation of the online learning policy brought more negative effect than positive was also big. These numbers brought down strikingly interesting findings, as discussed in this study. Keywords: Covid-19, Online Learning, high school students, English, learning impact